2003
DOI: 10.1177/135406880391004
|View full text |Cite
|
Sign up to set email alerts
|

Election Campaigning on the WWW in the USA and UK

Abstract: This article is a comparative analysis of British and American parties and candidate election campaigning on the World Wide Web during the Presidential and General Elections of 2000 and 2001, respectively. The central questions are twofold: (1) Do parties differ across the two systems in terms of how they use the Web as a campaign tool? (2) Does the Web promote a more balanced or equalized exposure for party messages than other media? A combination of interview data, content analysis of sites and analysis of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(37 citation statements)
references
References 21 publications
1
30
0
6
Order By: Relevance
“…However, research has shown similar trends in political engagement across Western Europe and North America, e.g. in the growth of web-based campaigning [13] and decline in youth engagement [11]. We thus have reason to believe that our findings may have broader applicability across this region, although further research would be needed to verify this.…”
Section: Limitationsmentioning
confidence: 90%
“…However, research has shown similar trends in political engagement across Western Europe and North America, e.g. in the growth of web-based campaigning [13] and decline in youth engagement [11]. We thus have reason to believe that our findings may have broader applicability across this region, although further research would be needed to verify this.…”
Section: Limitationsmentioning
confidence: 90%
“…De hecho, la actividad de los sitios web políticos varía sustancialmente dentro y fuera de los períodos electorales (Vaccari, 2008;Gibson et al, 2003; ValeraOrdaz; López-García, 2014), y lo mismo podría decirse del uso de las redes sociales (Vergeer; Hermans; Sams, 2011; Spyridou; Veglis, 2011; Macnamara; Sakinofsky; Beattie, 2012).…”
Section: Antecedentesunclassified
“…Many studies in US web campaign support the normalization theory as 'no-change' occurred (Norris, 2003), while studies on other countries such as the UK tend to be inconsistent (e.g. Gibson et al, 2003Gibson et al, & 2000Newell, 2001). Some researchers argued it depends on the national and institutional context (e.g.…”
Section: Scholarly Debate: Equalization and Normalization Theoriesmentioning
confidence: 99%
“…Some researchers argued it depends on the national and institutional context (e.g. Gibson et al, 2003). Kluver (2004) also notes that political culture plays a significant role in contextualising and limiting the effect of new media on political practice.…”
Section: Scholarly Debate: Equalization and Normalization Theoriesmentioning
confidence: 99%
See 1 more Smart Citation